Between gender and academic achievement: Creative thinking in mathematics problem solving among junior high school students - Abdussakir, Abdussakir; Chabibah, Rias; Yahya, Faridah Hanim; Ali, Fawad (Universitas Islam Negeri (UIN) Mataram, 2024)
[English]: Students’ creative thinking could be influenced by gender and academic achievement. Many studies have been carried out regarding levels of students’ creative thinking in solving problems based on gender and academic achievement, respectively. This study aims to understand differences in the levels of creative thinking of male and female students with high, medium, and low academic achievement in solving open-ended questions. This qualitative study involved 18 seventh-grade junior high school students selected based on gender differences and academic achievement. These students answered two open-ended problems on geometry and thought aloud about what they were thinking while answering the questions. Task-based interviews were conducted to explore students' answers. Data analysis shows that the level of students’ creative thinking, considering gender and academic achievement, appears to be inconsistent for different open-ended questions. However, there is a tendency that for figural questions, the higher the level of academic achievement, the higher the level of creative thinking, and male students outperform female students. This study also found differences in the level of creative thinking between the students based on the dimensions of creative thinking and the kinds of problems. The finding implies that gender differences and academic achievement are not adequate to determine the level of students’ creative thinking. [Bahasa]: Berpikir kreatif siswa dapat dipengaruhi oleh jenis kelamin dan prestasi akademik. Penelitian terdahulu mengenai tingkat berpikir kreatif siswa dalam memecahkan masalah kebanyakan berdasarkan jenis kelamin saja atau prestasi akademik saja. Penelitian ini bertujuan untuk mengetahui perbedaan tingkat berpikir kreatif siswa laki-laki dan perempuan dengan prestasi akademik tinggi, sedang, dan rendah dalam menyelesaikan soal terbuka. Penelitian kualitatif ini melibatkan 18 siswa SMP kelas 7 yang dipilih berdasarkan perbedaan jenis kelamin dan prestasi akademik. Siswa menjawab dua soal materi geometri dan menyuarakan apa yang mereka pikirkan selama menjawab soal tersebut. Wawancara berbasis tugas dilakukan untuk mengeksplorasi jawaban siswa. Hasil analisis data menunjukkan bahwa tingkat berpikir kreatif siswa dengan perbedaan jenis kelamin dan prestasi akademik ternyata tidak konsisten untuk soal yang berbeda. Namun, terdapat kecenderungan bahwa untuk soal yang memuat gambar, semakin tinggi tingkat prestasi akademik siswa laki-laki dan perempuan, semakin tinggi pula tingkat berpikir kreatifnya dan siswa laki-laki mengungguli siswa perempuan. Penelitian ini juga menemukan perbedaan tingkat berpikir kreatif siswa berdasarkan dimensi berpikir kreatif dan bentuk soal. Implikasi dari temuan ini adalah perbedaan jenis kelamin dan prestasi akademik tidak cukup untuk menentukan tingkat berpikir kreatif siswa.